Ethnoscience Study of Tabuik Pariaman, West Sumatra in Physics Learning - Febrian Virijai; Winny Liliawati; Ridwan Ridwan (U-Teach: Journal Education of Young Physics Teacher, 2024)
Tabuik is an annual event in Pariaman City, West Sumatra which has become a tourist attraction and icon of Pariaman City. The Tabuik event has many rituals in its implementation, starting from the manufacturing process to the ceremonial procession. This Tabuik event can be studied and found in ethnoscience to be integrated and implemented in Physics and Science learning at school. The research method used is qualitative research based on case studies. Data collection techniques include video observations of the process of making and ceremonial Tabuik Pariaman, and interviews. The results obtained from this research are that the Tabuik Pariaman ceremony process has the value of reconstructing knowledge through ethnoscience which can explain the local wisdom of the community. Tabuik ethnoscience can be implemented in Physics learning in the material of Force, Mechanical and Kinetic Energy, Moment of Inertia, Equilibrium of Rigid Bodies, and Elasticity. Implementation of Tabuik ethnoscience in science learning, namely in Biology learning about the classification of living things. Suggestions for further research include the implementation of Physics and Science learning from the culture and local wisdom of other regions